CONNECTION BETWEEN TWO COMPUTER NETWORKS USING USB PORT USB CABLE NETWORK / BRIDGE TO BRIDGE PL IC 2501 - Maryani Utomo; Nenny Anggraini, SKom., MT (Jurnal Sistem Komputer, 2007)
Scientific writing is about building a simple network between two computers withoutusing the ethernet card via a USB port. The problem that arises is the USB system isdesigned only to communicate with USB devices, so that the USB Host Controller ona computer can not be directly connected to the USB Host Controller on the othercomputer. By using a USB cable Network / Bridge as a USB device, the USB HostController can communicate with each other. USB Cable Network / Bridge has anelectronic circuit that functions as a regulator of the data traffic from the USB HostController on computer A to USB Host Controller on computer B and vice versa.Thus in building the network through a USB port USB devices required as a mediumof communication between the Host Controller.